Strategy Management of PT Agrapana Wukir Panca in Building Business Collaboration - Diana Ari Suryaningsih (Journal Research of Social Science, Economics, and Management, 2022)
The business concept now no longer uses independent thinking but has evolved into independence. Where business is not only and always leads to competition but also leads to collaboration. Business collaboration is the optimal choice in carrying out strategic management. PT Agrapana Wukir Panca is a company whose legalization status is still in the form of a Trade Unit. This study aims to find out how strategic management is applied at PT Agrapana Wukir Panca in building business collaboration. The research method used in this study is a library research method with a qualitative approach. The data is obtained from sources from articles, books, reports, and other research on strategic management and business collaboration. The results of the study found that the strategic management of PT Agrapana Wukir Panca which was applied in building business collaboration through three stages. First, the formulation of an audit strategy based on the company's mission and objectives. Both strategy implementations are based on effective resource allocation. And third, evaluate the strategy by monitoring.